Factors associated with the distribution and size of Adelges abietis (Homoptera: Adelgidae) galls on a sev- eral years old spruce (Picea abies) plantation - Pilichowski, Sebastian; Pazio, Damian; Giertych, Marian (Entomologica Fennica, 2015)
The eastern spruce gall adelgid (Adelges abietis) is a homopteran insect related to aphids. It forms pineapple-like pseudocone galls on Norway spruce (Picea abies) shoots, which are often deformed by them. The factors responsible for gall distribution within a tree crown are not clear. We investigated the distribution of galls in crowns on a spruce plantation. We assumed that the number and size of galls is dependent on the size of the tree, position on the crown, the type of shoot and its placement relative to the compass points. We also counted the larval chambers and related their number with gall size. We demonstrated that the largest galls are in the upper part of the crown and on the lateral shoots, and the number of chambers is closely related to the size of the galls. The level of shoot embrace has a significant impact on shoot deformation.